The Effect of Inflation, Interest Rates and Non-Performing Loans On Stock Returns Through Profitability In Banking Companies Indonesia Period 2018-2022 - Maesaroh Tiarawati, Neneng; Hertina, Dede (Devotion : Journal of Research and Community Service, 2024)
Even if the Indonesian economy has grown and the stock market has improved after COVID-19, banking stock returns in Indonesia have remained stagnant. The returns on Indonesian banking stocks in 2022 were much lower than in prior years. Identifying the internal and external variables that contributed to the fall in these shares is an obvious challenge. The purpose of this study is to investigate how return on assets (ROA) acts as a mediator between inflation, interest rates, non-performing loans, and stock returns. Thirty businesses make up the sample for this study, which employs testing methodologies including multiple regression and route analysis. Additionally, in order to find the indirect impact, the Sobel test must be used. This study found that stock returns are positively affected by inflation and return on assets, but unaffected by interest rates and non-performing loans. Unlike inflation and interest rates, return on assets can moderate the impact of non-performing loans on stock returns. stock performance. Things that could affect future returns should be carefully considered by investors.